Strategi Kepala Sekolah dalam Meningkatkan Mutu Lulusan - Nurasiah, Nurasiah; Hayati, Cut Intan; Zulkhairi, Zulkhairi; Diana, Novi (Yayasan Putroe Ceudah Aceh, 2025)
This study aims to describe the strategies implemented by school principals in improving the quality of graduates in educational units. The quality of graduates is one of the indicators of the success of an educational institution, which is influenced by various factors, including the leadership of the principal. This study uses a qualitative approach with a case study method. Data collection techniques are carried out through in-depth interviews, observations, and documentation. The results of the study show that school principals implement various strategies such as improving the quality of teachers through continuous training, improving the curriculum that is relevant to the needs of students, strengthening a positive school culture, and improving learning support facilities and infrastructure. In addition, the involvement of parents and the community is also a supporting factor in improving the quality of graduates. With the right strategy, school principals are able to encourage the creation of graduates who excel academically and non-academically.